Το Βυζάντιο ως ρωμαϊκό, ελληνικό και χριστιανικό - MAVROUDI, Maria (Byzantina Symmeikta, 2025)
Adequately discussing the Roman, Greek, and Christian aspects of Byzantium (how they were experienced by the Byzantines during a millennium, how other medieval civilizations and modernity perceived these qualities in Byzantine culture) would be a book-length project. A humble alternative is attempted here, in an effort to squeeze large topics within the confines of an article: a text foundational to the establishment of Byzantine studies as a modern academic discipline towards the end of the nineteenth century is used as a mirror of the field at that time, especially regarding a limited number of major and recurring topics in the modern historiography of Byzantium: its periodization, Roman self-identification, Christian identity, and relationship with the ancient Greek past. What is found there is compared with how twenty-first century scholarship approached the same questions. Some implications of the convergencies and differences for the present and future of the field are also drawn.